1956
DOI: 10.2172/4348116
|View full text |Cite
|
Sign up to set email alerts
|

LIGHT ISOTOPES OF BERKELIUM AND CALIFORNIUM (thesis)

Abstract: List of Illustrations 88 List of Tables 90 References 9I LIGHT ISOTOPES OF BERKELIUM AND CALIFORNIUM A. Chetham-Strode, Jr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1961
1961
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…241 Am was bombarded with α particles from the Argonne 152 cm cyclotron forming 242 Bk in the (α,3n) reaction. 242 later measurements were only reported in Ph.D. theses [104,105]. Although this assignment was very tentative it is currently being accepted as correct [106].…”
Section: Bkmentioning
confidence: 91%
“…241 Am was bombarded with α particles from the Argonne 152 cm cyclotron forming 242 Bk in the (α,3n) reaction. 242 later measurements were only reported in Ph.D. theses [104,105]. Although this assignment was very tentative it is currently being accepted as correct [106].…”
Section: Bkmentioning
confidence: 91%
“…The DWBA computer program 16 that was used is similar to one described previously 3,4 but differs in that it calculates the real and imaginary potentials independently, and in particular employs a derivative Woods-Saxon form 17 with the neutron real potential form factor the same as that for the proton. In the calculations all radial integrations extend to the origin.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…Indeed, it has been found that the DWBA theory with optical-model wave functions describes the reactions involving heavy targets 3 better than it does those involving lighter targets. 4 This situation is not unexpected since for heavier nuclei the optical model has greater validity and the neglect of compound-nucleus interference and decay is less serious.…”
Section: Introductionmentioning
confidence: 99%
“…These random correlations arise due to the manner in which the search is performed and the finite probability that an unwanted event can occur between the real recoil and α-particle event pair depending on the count rate of the individual pixels in the DSSDs. The half-lives obtained from the fits were A measurement of the electron-capture (EC) decay branch in 244,243 Cf was not possible in this work due to the long half-lives and very low α-decay branching ratios of 244 Bk [26] (T 1/2 = 4.35 (15) h, b α = 6(2) · 10 −3 %) and 243 Bk [27] (T 1/2 = 4.6(2) h, b α = 0.1%). Therefore, an α-decay branching ratio of b α = 14.0 % for 243 Cf that has been estimated in the literature [28,29] using data from [19] and [20] was adopted.…”
Section: A Lifetimes and α-Decay Branching Ratiosmentioning
confidence: 99%